In vitro establishment of blackberry (Rubus sp.) cultivar 'Xavante' - Pelizza,Tânia Regina (2016)
ABSTRACT: The objective of this study was to evaluate the in vitro establishment of 'Xavante' blackberry under different conditions of plant luminosity and concentrations of salts of MS medium. The maintenance of 'Xavante' blackberry plants in the absence of light, with the use of MS medium with salt concentrations of 75% and 100% reduce bacterial contamination and the percentage of explants oxidized and provide the highest percentage of surviving and established explants. The 50% salt dilution in MS medium is not recommended when plants are subjected to the absence of light due to the high percentage of oxidized explants and consequently lower survival and establishment.